Innovative financing channels: International evidence from initial coin offering and project start-up success factors - Ftiti, Zied; Hamza, Taher; Mnif, Zouhour; Louhichi, Waël (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This study investigates Initial Coin Offerings (ICOs) as an innovative financing channel, focusing on the factors influencing their success and the project start-up post-ICO. Using a hand-collected dataset of 410 ICOs from the 2016–2018 period, we analyze ICOs as a mechanism that enables startups to raise significant capital. We categorize the success factors into voluntary disclosure quality, team characteristics, deal characteristics, and country of issuance or geographic location. We also examine security and payment tokens to explore their differing impacts on ICO outcomes. Our study contributes to the extant literature by offering a comprehensive view of the factors that drive ICO success and those that explain post-ICO performance. Our study provides critical insights for investors, regulators, and entrepreneurs.